Sulfur-tolerant carbon dioxide methanation catalyst as well as preparation method and application thereof

By using nitrogen doping components such as mesoporous carbon, NiO and MoO3 in the catalyst and forming a Co-Zn coating on the surface, the problem of Ni-based catalysts being sensitive to sulfur is solved, achieving efficient, stable and heat-resistant resistance Sulfur methanation catalysts extend the service life of the catalyst and reduce costs.

CN119500216AActive Publication Date: 2025-02-25WUHUAN ENG +1

Patent Information

Application Number
CN202411527495.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-25
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

In the prior art, Ni-based catalysts are sensitive to sulfur species, resulting in catalyst deactivation and poisoning, and the activity and life of sulfur-resistant methanation catalysts are insufficient, limiting the progress of the process.

Method used

The carrier modifier is nitrogen-doped mesoporous carbon and/or silicon carbide, the active components are NiO and MoO3, the additives are CeO2 and MnO2, and a Co-Zn coating is formed on the catalyst surface to improve the sulfur resistance of the catalyst. Performance and activity.

Benefits of technology

It achieves the efficient, stable and heat-resistant properties of the catalyst, can maintain activity in high temperature and high sulfur environments, extend the service life of the catalyst, and reduce the investment and operating costs of the reactor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005109625570000201
    Figure BDA0005109625570000201
Patent Text Reader

Abstract

The invention discloses a sulfur-resistant carbon dioxide methanation catalyst as well as a preparation method and application thereof. A carrier of the catalyst comprises Al2O3 and ZrO2, a carrier modifier is nitrogen-doped mesoporous carbon and / or silicon carbide, active components comprise NiO and MoO3, auxiliaries comprise CeO2 and MnO2, and a coating is a Co-Zn coating. The content of Al2O3 is 10-70 wt%, the content of ZrO2 is 2-15 wt%, the content of the carrier modifier is 1-75 wt%, the content of the active component is 10-50 wt%, and the content of the auxiliary agent is 1-5 wt%. The catalyst is high in reaction efficiency, good in stability, high in selectivity and good in heat resistance; during use, different catalysts are filled in a layered manner, the temperature rise of a bed layer is mild, the hot-spot temperature is low, and a local high-temperature region is avoided, so that sulfur poisoning and sintering inactivation of the catalyst are avoided, the investment and operation cost is reduced, the service life of the catalyst is prolonged, and the operation safety of the device is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of methane catalysts, and in particular relates to a sulfur-resistant carbon dioxide methanation catalyst, a preparation method and an application thereof. Background Art

[0002] With the increasing depletion of non-renewable energy sources such as oil and coal, and the environmental deterioration caused by the rising concentration of greenhouse gases in the atmosphere, the conversion of greenhouse gas carbon dioxide into high-value-added chemical products has become a hot topic of research in domestic and foreign academic circles. Among them, the use of carbon dioxide hydrogenation to synthesize methane can not only reduce the concentration of carbon dioxide in the atmosphere, but the methane produced can also be used as fuel, which can alleviate the energy problem to a certain extent. In addition, methane is also a commonly used chemical raw material, which can be further used to produce chemical products such as acetylene and synthetic ammonia. Therefore, the development of an efficient carbon dioxide methanation technology has great practical significance.

[0003] CO2(g)+4H2(g)→CH4(g)+2H2 O(g)△Hθ298K=-165kJ / mol

[0004] △Gθ298K=-113kJ / mol

[0005] Among the existing industrial methanation catalysts, the supported Ni-based catalysts have the best effect. However, Ni-based catalysts are very sensitive to surface carbon deposition and sulfur species, which leads to catalyst deactivation and poisoning. When using Ni-based catalysts, acidic gases such as H2S contained in the raw gas must be removed to reduce their content to less than 0.1ppm. Carbon dioxide gas from general industrial sources contains sulfur, so before methanation, the carbon dioxide gas must be subjected to high-cost desulfurization and purification treatment.

[0006] At present, most sulfur-resistant methanation catalysts are supported catalysts, using Mo, W, Ni and Co as active components of the catalyst, Al2O3, CeO2, ZrO2, SiO2 and TiO2 as carriers, and K, La, Cr and Fe as additives. However, their methanation catalytic activity is not high, and the general CO conversion rate is 50% to 90%, and the CH4 selectivity is only 60% to 70%. The activation temperature is also relatively high, generally above 450 degrees. And most of them have not been tested for catalyst life or have a short life. In particular, most catalysts are not resistant to high temperatures, which greatly limits the progress of sulfur-resistant methanation technology. Moreover, under high CO2 content in the raw gas, the CO conversion rate drops to 20% to 50%, and the CH4 selectivity is only 30% to 50%. However, there are few reports on sulfur-resistant methanation catalysts for carbon dioxide. Patent CN103551053A discloses a copper-based carbon dioxide methanation catalyst and its preparation method, but the patent does not mention sulfur resistance. Patent CN 112642440 B discloses a sulfur-resistant carbon dioxide methanation catalyst, but the catalyst uses the noble metal Rh as an active component and has a high manufacturing cost.

[0007] From a thermodynamic point of view, lowering the methanation operating temperature is conducive to the forward reaction equilibrium. Theoretical calculations show that when the inlet CO+CO2 content is less than 20%, the CO / CO2 equilibrium conversion rate is ≥99% within the operating temperature range of ≤320°C and the operating pressure range of 2.5-4.5MPa. Therefore, by adopting an effective temperature control reactor method, the bed outlet temperature is controlled within 320°C, and only a single reactor is needed to achieve efficient CO / CO2 conversion, reducing device investment and operating energy consumption.

[0008] Patent CN110237778A discloses an isothermal reactor and a process method for convenient catalyst replacement, which is characterized in that the reactor adopts a concentric circle design, the catalyst is loaded in an annular screen, the screen is loaded into the concentric circle reactor as a whole, and the catalyst is disassembled and assembled as a whole, with the focus on the structural characteristics of the reactor.

[0009] Patent CN113289663A discloses a method for preparing a methanation catalyst for an isothermal fixed bed, in which a mesoporous carrier is prepared by using silicon nitride and alumina.

[0010] Patent CN204247177U discloses an adiabatic-isothermal methanation reactor, in which an adiabatic section and an isothermal section are arranged, and the isothermal section is a shell-and-tube structure.

[0011] In previous public patents, the starting point of developing catalysts was to improve the activity of the catalyst. However, studies have shown that the intrinsic rate of the CO2 methanation reaction is very fast. In industrial adiabatic fixed-bed reactors, hot spots appear at 1 / 5 to 1 / 8 of the bed position. The catalyst bed temperature decreases behind the hot spot, making it easy for local high-temperature areas to appear in the methanation catalyst bed, and the catalyst is easily sintered. At the same time, the catalyst reaction performance on the rear side is not reflected.

[0012] In actual operation, if the temperature control in the methanation reactor is not properly controlled, it is also very easy to cause the bed to overheat, burn through the internal components of the reactor, and cause the catalyst to sinter and deactivate at high temperature. Therefore, in order to make the methanation reactor run smoothly, the heat generated can be effectively removed, and the purpose of controlling the bed temperature uniformity is achieved, it is necessary to study the use and loading method of the methanation catalyst from a kinetic perspective. Summary of the invention

[0013] The purpose of the present invention is to solve the above technical problems and provide a sulfur-resistant carbon dioxide methanation catalyst with high efficiency, good stability, high selectivity and good heat resistance, as well as a preparation method and application.

[0014] To achieve the above-mentioned purpose, the present invention provides a sulfur-resistant carbon dioxide methanation catalyst, characterized in that: the catalyst comprises a carrier, a carrier modifier, an active component, an auxiliary agent and a coating; the carrier comprises Al2O3 and ZrO2, the carrier modifier is nitrogen-doped mesoporous carbon and / or silicon carbide, the active component comprises NiO and MoO3, the auxiliary agent comprises CeO2 and MnO2, and the coating is a Co-Zn coating; in terms of the total weight percentage of the catalyst: the content of Al2O3 is 10-70wt%, the content of ZrO2 is 2-15wt%, the content of the carrier modifier is 1-75wt%, the content of the active component is 10-50wt%, and the mass ratio of NiO:MoO3 is 1-5:0-1, the content of the auxiliary agent is 1-5wt%, and the mass ratio of CeO2:MnO2 is 1-5:1, the content of the Co-Zn coating is 0-10wt%, and the mass ratio of CoO:ZnO is 1:1-3.

[0015] Furthermore, when the support modifier is a mixture of nitrogen-doped mesoporous carbon and silicon carbide, the mass ratio of nitrogen-doped mesoporous carbon to silicon carbide is 1-3:1-3.

[0016] Furthermore, the nitrogen-doped mesoporous carbon has a nitrogen content of 1.5-12% and a specific surface area of ​​800-1200 m 2 / g, and the average pore size is 4 to 8.1 nm.

[0017] A method for preparing the catalyst as described above is also provided as follows:

[0018] 1) stirring and ultrasonically dispersing the support modifier in the salt solution to form a suspension, and heating the suspension to 50-80° C. for standby use; dissolving the precursor salt in deionized water to form a precursor salt solution, heating the precursor salt solution and the precipitant solution to 50-80° C. respectively, and dripping the precursor salt solution and the precipitant solution into the suspension in parallel for precipitation reaction, maintaining the pH of the solution at 7-8 and continuously stirring;

[0019] 2) Add cobalt and zinc salt solutions to the solution, add alkaline precipitant, maintain the pH of the solution at 7-8, and continue stirring;

[0020] 3) After precipitation, the catalyst is aged, washed, filtered, dried, calcined and then formed into tablets to obtain the desired catalyst.

[0021] Furthermore, in the step 1), the molar ratio of the precursor salt to the precipitant is 0.1 to 10:1, the mass concentration of the precursor salt solution is 0.5 to 5%; and the solid-liquid mass ratio of the suspension is 1:20 to 1:50.

[0022] Furthermore, the precursor salt is composed of nickel nitrate, manganese nitrate, cerium nitrate, aluminum nitrate, zirconium nitrate and ammonium molybdate; the Co salt is cobalt nitrate, and the Zn salt is zinc nitrate; and the precipitant is at least one of sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate.

[0023] Furthermore, in the step 3), the calcination temperature is 300-600° C., the calcination time is 4-12 hours, and the calcination atmosphere is nitrogen.

[0024] Finally, an application of the catalyst as described above is provided, wherein a catalyst active layer is loaded in a reactor, and an inert filler layer is arranged at both ends of the catalyst active layer, wherein the catalyst active layer is composed of a WH-HS catalyst and / or a WH-LS catalyst and / or a WH-HM catalyst;

[0025] The WH-HS catalyst is a highly sulfur-resistant methanation catalyst: the content of Al2O3 is 10-30wt%, the content of ZrO2 is 2-5wt%; the content of the carrier modifier is 40-70wt%, the mass ratio of nitrogen-doped mesoporous carbon: silicon carbide is 1-3:1-3; the content of the active component is 10-30wt%, the mass ratio of NiO:MoO3 is 1-3:1; the content of the auxiliary agent is 1-5wt%, the mass ratio of CeO2:MnO2 is 1-5:1; the content of the Co-Zn coating is 5-10wt%, and the mass ratio of CoO:ZnO is 1:1-3;

[0026] WH-LS catalyst is a low sulfur-resistant methanation catalyst: the content of Al2O3 is 20-50wt%, the content of ZrO2 is 2-10wt%, the content of carrier modifier is 15-30wt%, the mass ratio of nitrogen-doped mesoporous carbon: silicon carbide is 1-3:1-3; the content of active component is 20-40wt%, the mass ratio of NiO:MoO3 is 5-10:1; the content of auxiliary agent is 1-5wt%, the mass ratio of CeO2:MnO2 is 1-5:1; the content of Co-Zn coating is 1-5wt%, and the mass ratio of CoO:ZnO is 1:1-3;

[0027] WH-HM catalyst is a highly active methanation catalyst: the content of Al2O3 is 40-60wt%, the content of ZrO2 is 2-10wt%, the content of carrier modifier is 1-10wt%, the mass ratio of nitrogen-doped mesoporous carbon: silicon carbide is 1-3:1-3, the content of active component NiO is 25-50wt%, the content of auxiliary agent is 1-5wt%, and the mass ratio of CeO2:MnO2 is 1-5:1.

[0028] Furthermore, the catalyst active layers are 3 to 6 layers, all arranged along the airflow direction; the catalyst active layer of the first layer is a WH-HS catalyst, the catalyst active layer of the second layer is a WH-LS catalyst, and the catalyst active layers of the remaining layers are mixed catalysts of WH-HM catalysts and WH-LS catalysts, the mass fraction ratio of WH-HM catalysts to WH-LS catalysts is 3:0.1 to 1, and the mass fraction ratio of WH-HM catalysts increases layer by layer along the airflow direction; the catalysts in the catalyst active layers of the same layer have the same shape. The reactor is a shell-and-tube temperature-controlled reactor, the catalyst is loaded in the shell layer, and the water channel supplies and transfers heat through the tube layer.

[0029] Furthermore, in the reactor: the bed temperature is 240-290°C, the hot spot temperature is 380-500°C, and the reactor gas outlet outflow temperature is 250-300°C.

[0030] By using metal nitrate as a catalyst, the microporous activated carbon is expanded into mesoporous carbon, and melamine and urea are used as nitrogen sources for nitrogen doping modification. Mesoporous carbon has a developed mesoporous structure, which is conducive to the molecular diffusion of reactants and products, and is also conducive to the transfer of reaction heat; nitrogen doped in mesoporous carbon is conducive to promoting electron transfer and improving the reduction ability of the catalyst; nitrogen doping is conducive to the loading and dispersion of Ni, promoting the reduction of Ni, and is conducive to improving the low-temperature activity and high-temperature stability of the catalyst.

[0031] The catalyst of the present invention uses ZrO2-Al2O3 and nitrogen-doped mesoporous carbon or SiC as a composite carrier. The addition of ZrO2 improves the electron transfer ability and acidity of the Al2O3 carrier. The surface of the nitrogen-doped material can adsorb a large amount of hydrogen and transfer it to the active site on the catalyst surface to increase the rate of the hydrogenation reaction. It is beneficial to improve the activity of the catalyst in the low-temperature methanation reaction of CO2. It also has the characteristics of excellent thermal conductivity and electron transfer performance, and at the same time improves the low-temperature activity and high-temperature resistance of the catalyst; the hydrophobicity of the nitrogen-doped mesoporous carbon material is beneficial to desorbing water generated after the methanation of carbon dioxide, and improves the methanation performance of carbon dioxide at low temperature; the introduction of nitrogen-doped mesoporous carbon interacts with the Ni active component, promotes the effective dispersion of the active component Ni of the molded catalyst, the Ni grains after calcination are small, the reaction activation temperature is low, and it has good low-temperature reaction activity, which is particularly suitable for methanation heat transfer reactors, and can effectively reduce the investment and operation costs of reactor equipment. At the same time, after the nitrogen-doped mesoporous carbon is introduced into the catalyst, carbon sites are formed on the catalyst surface, the mesoporous channels are conducive to heat and mass transfer, and the nitrogen doping promotes the electron mobility of the surface. The formed carbon sites inhibit the generation and further expansion of carbon deposits, and improve the catalyst's resistance to carbon deposits. The in-situ introduction of SiC into the catalyst further enhances the catalyst's thermal conductivity. The introduction of Ce, Mn, and Mo additives further enhances the activity and stability of the catalyst; the introduction of Mo enhances the catalyst's ability to adsorb sulfur, and sulfur is preferentially adsorbed on Mo, thereby protecting the Ni-based active centers. In the catalyst preparation process, the present invention creatively introduces a Co-Zn coating by staged precipitation, and the Co-Zn composite coating exhibits a strong adsorption capacity for sulfides, thereby improving the catalyst's sulfur resistance and protecting the catalyst's Ni active centers.

[0032] Due to the introduction of Mo and Co-Zn, the activity of the catalyst is affected to a certain extent. Combined with the temperature-controlled methanation technology, the catalyst active layer is composed of a mixed high-sulfur-resistant WH-HS catalyst, a low-sulfur-resistant WH-LS, and a mixture of WH-LS and a high-activity WH-HM catalyst. Among them, the main active component of the WH-HM catalyst is a composite oxide of nickel oxide-manganese oxide-cerium oxide-molybdenum oxide. The use of nickel oxide and cerium oxide here is considered that the composite rare earth additive is beneficial to improve the interaction with Ni species and form NiO physical species, promote active CO2 molecules at low temperatures, and contain Mo and Co-Zn coatings, which are beneficial to improve the adsorption capacity of sulfides. The catalyst also has nitrogen-doped mesoporous carbon or SiC, which further improves the thermal conductivity of the catalyst and avoids heat accumulation; the WH-LS catalyst contains lower sulfur-resistant components Mo and Co-Zn than the WH-HS catalyst, so it has higher methanation performance. ; The WH-HM catalyst does not contain sulfur-resistant components, so the catalyst activity is higher. Here, the three catalysts are mixed to achieve the purpose of reasonably controlling the reaction temperature of the catalyst bed, avoiding the influence of hydrogen sulfide in the catalyst, avoiding the generation of temperature runaway or local hot spots, extending the service life of the catalyst, and thus exerting a synergistic catalytic effect.

[0033] In addition, in the present invention, 3 to 6 layers of catalyst active layers are sequentially arranged along the direction of gas flow. In addition to arranging multiple layers of catalyst active layers, the mixing ratio of the two catalysts in each layer is also limited. Based on the kinetic perspective, the hot spot temperature of the catalyst is closely related to the intrinsic activity of the catalyst. For this reason, the amount of WH-HM catalyst with high methanation reaction activity is increased layer by layer along the gas flow direction, while the amount of WH-LS catalyst with high thermal conductivity and suitable methanation activity sulfur resistance is gradually reduced. This can effectively lengthen the distance between the zero-meter temperature and the hot spot temperature, ensure that the bed temperature rise is relatively gentle, and make the hot spot temperature appear in the second layer, the third layer, or even the catalyst active layer further back, and no obvious displacement occurs, so as to achieve the purpose of reducing the hot spot temperature of the bed, which can improve the single-pass conversion rate of the catalyst, and at the same time avoid the catalyst sintering deactivation and extend the service life. The catalysts in the same catalyst active layer have the same shape, so that the catalysts in each bed are evenly mixed, and it is helpful to load in sections, so as to achieve the purpose of facilitating industrial loading and use.

[0034] The characteristic of the induction can make the methanation catalyst resistant to about 5ppm of sulfur and have stable methanation performance, and the methanation effect is good; the filling method of the present invention can effectively reduce the hot spot temperature of the bed, reduce the concentration gradient of the catalyst axial direction, slow down the intensity of the methanation reaction, realize gentle heating in the bed, effectively avoid the risk of local high temperature zone and catalyst sintering deactivation, and extend the service life of the catalyst and the reactor; the filling structure of the present invention does not need to change the reactor structure, can withstand a certain amount of H2S, thereby reducing purification investment and operating costs, when the CO2 content at the reaction gas inlet is within 20%, a single reactor can be used to achieve efficient conversion of CO2, the bed temperature rise is small, the safety is high, there is no need to introduce circulating gas or steam dilution, energy saving and consumption reduction, and also effectively reduce equipment investment and operating costs.

[0035] Compared with the prior art, the beneficial effects of the present invention are as follows: the sulfur-resistant carbon dioxide methanation catalyst of the present invention has high reaction efficiency, good stability, high selectivity and good heat resistance; different catalysts are loaded in layers during use, the bed temperature rises gently and the hot spot temperature is low, thus avoiding the generation of local high-temperature areas, avoiding catalyst sulfur poisoning and sintering deactivation, reducing investment and operating costs, extending the catalyst life, and improving the safety of device operation. DETAILED DESCRIPTION

[0036] The present invention will be further described below in conjunction with specific embodiments.

[0037] Example 1

[0038] WH-HS catalyst: 25 g nitrogen-doped mesoporous carbon (size > 500 mesh, 1100 m 2 / g, average pore size 5.5nm, nitrogen content 5%, of which pyridinic nitrogen 44.51%, pyrrolic nitrogen 26.59%, graphite nitrogen 20.52%, oxidized nitrogen 8.38%) and 25g SiC (size> 500 mesh) were dispersed at high speed in a sodium nitrate salt solution (the mass concentration of the sodium nitrate salt solution was 5%, the ultrasonic frequency was controlled to be 40kHz, and the power was 800kW) to form a suspension (the solid-liquid mass ratio of the suspension was 1:20); then the suspension was heated to 50°C, 58.2g nickel nitrate, 95.6g aluminum nitrate, 6.9g zirconium nitrate, 4.1g manganese nitrate, 7.6g cerium nitrate, and 12.3g ammonium molybdate were configured into a precursor salt solution, and sodium carbonate was configured as a precipitant solution (take The molar ratio of the precursor salt to sodium carbonate is 0.1:1), which is preheated to 80°C by electric heating, and then dripped into the suspension in parallel (the dripping speed is completed within 50 minutes, and the stirring speed is 600rpm), and the precipitation reaction is started, and the pH of the solution is maintained at 7-8 and stirred for 1 hour; a salt solution of cobalt and zinc, containing 5.8g of cobalt nitrate and 16.7g of zinc nitrate, is added to the above solution, and an alkaline precipitant is added to maintain the pH of the solution at 7-8, and stirring is continued for 1-2 hours; the precipitate is filtered, pulped, and washed for multiple cycles until the conductivity of the filtrate is 50μS / cm, and then dried, and then calcined to obtain a catalyst powder; the calcination temperature is 300°C, the calcination time is 12h, and the calcination atmosphere is nitrogen.

[0039] Calculated by the mass of oxides, nickel oxide, molybdenum oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide, cobalt oxide and zinc oxide account for 15%, 10%, 13%, 2%, 1%, 3%, 1.5% and 4.5% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 25% of the catalyst mass, respectively.

[0040] WH-LS catalyst: The preparation method is the same as that of WH-HS catalyst, the difference is that the amount of Mo, Co and Zn added is different.

[0041] The catalyst powder, calculated by the mass of oxides, nickel oxide, molybdenum oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide, cobalt oxide and zinc oxide account for 25%, 5%, 40%, 4%, 1%, 3%, 0.5% and 1.5% of the catalyst mass respectively, and nitrogen-doped mesoporous carbon and SiC account for 10% of the catalyst mass each.

[0042] WH-HM catalyst: The preparation method is the same as that of WH-HS catalyst, but it does not contain Mo, Co, or Zn.

[0043] The catalyst powder, calculated by the mass of oxides, comprises nickel oxide, aluminum oxide, zirconium oxide, manganese oxide and cerium oxide respectively accounting for 35%, 50%, 5%, 1% and 4% of the catalyst mass, nitrogen-doped mesoporous carbon accounting for 2% of the catalyst mass and SiC accounting for 3%.

[0044] Catalyst performance test: The above catalyst was reduced at 500°C for 10 hours and then the carbon dioxide methanation reaction performance was evaluated. The reaction evaluation set the reaction temperature to 250°C, the reaction pressure to 2.5MPa, the raw gas composition to 20%-CO, 80%-H2, and the H2S content to 20ppm. The reaction results are shown in Table 1.

[0045] The reactor filling structure is: 2 layers of inert filler layers (M layer and N layer) and 6 layers of catalyst active layers (from top to bottom, A layer, B layer, C layer, D layer, E layer, and F layer). The first layer A is filled with WH-HS catalyst, which is in the shape of a four-hole wheel and has an outer diameter of 6mm; the second layer B is filled with WH-LS, which is cylindrical and has an outer diameter of 3mm; the third layer C is filled with WH-HM and WH-LS catalysts at a loading ratio of 3:1, both catalysts are spherical, and the outer diameter of the catalyst is 4mm; the fourth layer D is filled with WH-HM and WH-LS catalysts at a loading ratio of 5:1, the fifth layer E is filled with WH-HM and WH-LS catalysts at a loading ratio of 6:1, both catalysts are cylindrical, and the outer diameter of the catalyst is 3mm; the sixth layer F is filled with WH-HM and WH-LS catalysts at a loading ratio of 12:1, both catalysts are spherical, and the outer diameter of the catalyst is 3mm; Catalyst loading performance test:

[0046] The reaction pressure is 2.5MPa, the raw gas composition is 15% -CO2, the hydrogen-carbon ratio is 4:1, the rest are N2 / CH4 and other components, the H2S content is 5ppm, and it is preheated to 250℃ before entering the catalyst active layer. The hot spot temperature appears in the third layer (C layer) with a temperature of 385℃. After passing through the F layer, the gas temperature is 280℃, the CO2 conversion rate is ≥99.5%, the CH4 selectivity is ≥99.5%, and it runs continuously for 1000h. The hot spot position has not moved significantly and the catalyst activity remains unchanged.

[0047] Example 2

[0048] WH-HS catalyst: 25 g nitrogen-doped mesoporous carbon (size > 500 mesh, 1100 m 2 / g, average pore size 5.5nm, nitrogen content 5%, of which pyridinic nitrogen 44.51%, pyrrolic nitrogen 26.59%, graphite nitrogen 20.52%, oxidized nitrogen 8.38%) and 25g SiC (size> 500 mesh) were dispersed at high speed in a sodium nitrate salt solution (the mass concentration of the sodium nitrate salt solution was 5%, the ultrasonic frequency was controlled to be 40kHz, and the power was 800kW) to form a suspension (the solid-liquid mass ratio of the suspension was 1:20); then the suspension was heated to 50°C, 58.2g nickel nitrate, 95.6g aluminum nitrate, 6.9g zirconium nitrate, 4.1g manganese nitrate, 7.6g cerium nitrate, and 12.3g ammonium molybdate were configured into a precursor salt solution, and sodium carbonate was configured as a precipitant solution (take The molar ratio of the precursor salt to sodium carbonate is 0.1:1), which is preheated to 80°C by electric heating, and then dripped into the suspension in parallel (the dripping speed is completed within 50 minutes, and the stirring speed is 600rpm), and the precipitation reaction is started, and the pH of the solution is maintained at 7-8 and stirred for 1 hour; a salt solution of cobalt and zinc, containing 5.8g of cobalt nitrate and 16.7g of zinc nitrate, is added to the above solution, and an alkaline precipitant is added to maintain the pH of the solution at 7-8, and stirring is continued for 1-2 hours; the precipitate is filtered, pulped, and washed for multiple cycles until the conductivity of the filtrate is 50μS / cm, and then dried, and then calcined to obtain a catalyst powder; the calcination temperature is 400°C, the calcination time is 10 hours, and the calcination atmosphere is nitrogen.

[0049] Calculated by the mass of oxides, nickel oxide, molybdenum oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide, cobalt oxide and zinc oxide account for 15%, 10%, 13%, 2%, 1%, 3%, 1.5% and 4.5% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 25% of the catalyst mass, respectively.

[0050] WH-LS catalyst: The preparation method is the same as that of WH-HS catalyst, the difference is that the amount of Mo, Co and Zn added is different.

[0051] The catalyst powder, calculated by the mass of oxides, nickel oxide, molybdenum oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide, cobalt oxide and zinc oxide account for 25%, 5%, 40%, 4%, 1%, 3%, 0.5% and 1.5% of the catalyst mass respectively, and nitrogen-doped mesoporous carbon and SiC account for 10% of the catalyst mass each.

[0052] WH-HM catalyst: The preparation method is the same as that of WH-HS catalyst, but it does not contain Mo, Co, or Zn.

[0053] The catalyst powder, calculated by the mass of oxides, comprises nickel oxide, aluminum oxide, zirconium oxide, manganese oxide and cerium oxide respectively accounting for 35%, 50%, 5%, 1% and 4% of the catalyst mass, nitrogen-doped mesoporous carbon accounting for 2% of the catalyst mass and SiC accounting for 3%.

[0054] Catalyst performance test: The above catalyst was reduced at 500°C for 10 hours and then the carbon dioxide methanation reaction performance was evaluated. The reaction evaluation set the reaction temperature to 250°C, the reaction pressure to 2.5MPa, the raw gas composition to 20%-CO, 80%-H2, and the H2S content to 20ppm.

[0055] The reactor filling structure is: 2 layers of inert filler layers (M layer and N layer) and 4 layers of catalyst active layers (A layer, B layer, C layer, D layer from top to bottom). The first layer A is filled with WH-HS catalyst, which is in the shape of a four-hole wheel and has an outer diameter of 6mm; the second layer B is filled with WH-LS, which is cylindrical and has an outer diameter of 3mm; the third layer C is filled with WH-HM and WH-LS catalysts in a 3:1 ratio, both catalysts are spherical, and the outer diameter of the catalyst is 4mm; the fourth layer D is filled with WH-HM and WH-LS catalysts in a 6:1 ratio, and the catalysts used are all cylindrical, with an outer diameter of 3mm;.

[0056] Catalyst loading performance test:

[0057] The reaction pressure is 2.5MPa, the raw gas composition is 15% -CO2, the hydrogen-carbon ratio is 4:1, the rest are N2 / CH4 and other components, the H2S content is 5ppm, and it is preheated to 250℃ before entering the catalyst active layer. The hot spot temperature appears in the third layer (C layer) at 400℃, and the gas temperature after passing through the D layer is 290℃. The CO2 conversion rate is ≥99.5%, and the CH4 selectivity is ≥99.5%. After continuous operation for 1000h, the hot spot position has not moved significantly and the catalyst activity remains unchanged.

[0058] Example 3

[0059] WH-HS catalyst: 25 g nitrogen-doped mesoporous carbon (size > 500 mesh, 1100 m 2 / g, average pore size 5.5nm, nitrogen content 5%, of which pyridinic nitrogen 44.51%, pyrrolic nitrogen 26.59%, graphite nitrogen 20.52%, oxidized nitrogen 8.38%) and 25g SiC (size> 500 mesh) were dispersed at high speed in a sodium nitrate salt solution (the mass concentration of the sodium nitrate salt solution was 5%, the ultrasonic frequency was controlled to be 40kHz, and the power was 800kW) to form a suspension (the solid-liquid mass ratio of the suspension was 1:20); then the suspension was heated to 50°C, 58.2g nickel nitrate, 95.6g aluminum nitrate, 6.9g zirconium nitrate, 4.1g manganese nitrate, 7.6g cerium nitrate, and 12.3g ammonium molybdate were configured into a precursor salt solution, and sodium carbonate was configured as a precipitant solution (take The molar ratio of the precursor salt to sodium carbonate is 0.1:1), which is preheated to 80°C by electric heating, and then dripped into the suspension in parallel (the dripping speed is completed within 50 minutes, and the stirring speed is 600rpm), the precipitation reaction is started, the pH of the solution is maintained at 7-8 and stirring is continued for 1 hour; cobalt and zinc salt solution, containing 5.8g of cobalt nitrate and 16.7g of zinc nitrate, is added to the above solution, and an alkaline precipitant is added to maintain the pH of the solution at 7-8, and stirring is continued for 1-2 hours; the precipitate is filtered, pulped, and washed for multiple cycles until the conductivity of the filtrate is 50μS / cm, and then dried, and then calcined to obtain a catalyst powder; the calcination temperature is 500°C, the calcination time is 8h, and the calcination atmosphere is nitrogen.

[0060] Calculated by the mass of oxides, nickel oxide, molybdenum oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide, cobalt oxide and zinc oxide account for 15%, 10%, 13%, 2%, 1%, 3%, 1.5% and 4.5% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 25% of the catalyst mass, respectively.

[0061] WH-LS catalyst: The preparation method is the same as that of WH-HS catalyst, except that the added amounts of Mo, Co and Zn are different.

[0062] The catalyst powder, calculated by the mass of oxides, nickel oxide, molybdenum oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide, cobalt oxide and zinc oxide account for 25%, 5%, 40%, 4%, 1%, 3%, 0.5% and 1.5% of the catalyst mass respectively, and nitrogen-doped mesoporous carbon and SiC account for 10% of the catalyst mass each.

[0063] WH-HM catalyst: The preparation method is the same as that of WH-HS catalyst, but it does not contain Mo, Co, or Zn.

[0064] The catalyst powder, calculated by the mass of oxides, comprises nickel oxide, aluminum oxide, zirconium oxide, manganese oxide and cerium oxide respectively accounting for 35%, 50%, 5%, 1% and 4% of the catalyst mass, nitrogen-doped mesoporous carbon accounting for 2% of the catalyst mass and SiC accounting for 3%.

[0065] Catalyst performance test: The above catalyst was reduced at 500°C for 10 hours and then the carbon dioxide methanation reaction performance was evaluated. The reaction evaluation set the reaction temperature to 250°C, the reaction pressure to 2.5MPa, the raw gas composition to 20%-CO, 80%-H2, and the H2S content to 20ppm.

[0066] The reactor packing structure is: 2 layers of inert filler layers (M layer and N layer) and 5 layers of catalyst active layers (A layer, B layer, C layer, D layer, E layer from top to bottom). The first layer A is filled with WH-HS catalyst, which is in the shape of a four-hole wheel and has an outer diameter of 6mm; the second layer B is filled with WH-LS, which is in the shape of a cylinder and has an outer diameter of 3mm; the third layer C is filled with WH-HM and WH-LS catalysts at a ratio of 3:1, both catalysts are spherical, and the outer diameter of the catalyst is 4mm; the fourth layer D is filled with WH-HM and WH-LS catalysts at a ratio of 5:1, both catalysts are cylindrical, and the outer diameter of the catalyst is 3mm; the fifth layer E is filled with WH-HM and WH-LS catalysts at a ratio of 6:1, both catalysts are spherical, and the outer diameter of the catalyst is 3mm. .

[0067] Catalyst loading performance test:

[0068] The reaction pressure is 2.5MPa, the raw gas composition is 15% -CO2, the hydrogen-carbon ratio is 4:1, the rest are N2 / CH4 and other components, the H2S content is 5ppm, and it is preheated to 250℃ before entering the catalyst active layer. The hot spot temperature appears in the third layer (C layer) at 395℃, and the gas temperature after passing through the E layer is 288℃. The CO2 conversion rate is ≥99.5%, and the CH4 selectivity is ≥99.5%. After continuous operation for 1000h, the hot spot position has not moved significantly and the catalyst activity remains unchanged.

[0069] Example 4

[0070] WH-HS catalyst: 25 g nitrogen-doped mesoporous carbon (size > 500 mesh, 1100 m 2 / g, average pore size 5.5nm, nitrogen content 5%, of which pyridinic nitrogen 44.51%, pyrrolic nitrogen 26.59%, graphite nitrogen 20.52%, oxidized nitrogen 8.38%) and 25g SiC (size> 500 mesh) were dispersed at high speed in a sodium nitrate salt solution (the mass concentration of the sodium nitrate salt solution was 5%, the ultrasonic frequency was controlled to be 40kHz, and the power was 800kW) to form a suspension (the solid-liquid mass ratio of the suspension was 1:20); then the suspension was heated to 50°C, 58.2g nickel nitrate, 95.6g aluminum nitrate, 6.9g zirconium nitrate, 4.1g manganese nitrate, 7.6g cerium nitrate, and 12.3g ammonium molybdate were configured into a precursor salt solution, and sodium carbonate was configured as a precipitant solution (take The molar ratio of the precursor salt to sodium carbonate is 0.1:1), which is preheated to 80°C by electric heating, and then dripped into the suspension in parallel (the dripping speed is completed within 50 minutes, and the stirring speed is 600rpm), the precipitation reaction is started, the pH of the solution is maintained at 7-8 and stirring is continued for 1 hour; cobalt and zinc salt solution, containing 5.8g of cobalt nitrate and 16.7g of zinc nitrate, is added to the above solution, and an alkaline precipitant is added to maintain the pH of the solution at 7-8, and stirring is continued for 1-2 hours; the precipitate is filtered, pulped, and washed for multiple cycles until the conductivity of the filtrate is 50μS / cm, and then dried, and then calcined to obtain a catalyst powder; the calcination temperature is 500°C, the calcination time is 8h, and the calcination atmosphere is nitrogen.

[0071] Calculated by the mass of oxides, nickel oxide, molybdenum oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide, cobalt oxide and zinc oxide account for 15%, 10%, 13%, 2%, 1%, 3%, 1.5% and 4.5% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 25% of the catalyst mass, respectively.

[0072] WH-LS catalyst: The preparation method is the same as that of WH-HS catalyst, the difference is that the amount of Mo, Co and Zn added is different.

[0073] The catalyst powder, calculated by the mass of oxides, nickel oxide, molybdenum oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide, cobalt oxide and zinc oxide account for 25%, 5%, 40%, 4%, 1%, 3%, 0.5% and 1.5% of the catalyst mass respectively, and nitrogen-doped mesoporous carbon and SiC account for 10% of the catalyst mass each.

[0074] WH-HM catalyst: The preparation method is the same as that of WH-HS catalyst, but it does not contain Mo, Co, or Zn.

[0075] The catalyst powder, calculated by the mass of oxides, comprises nickel oxide, aluminum oxide, zirconium oxide, manganese oxide and cerium oxide respectively accounting for 35%, 50%, 5%, 1% and 4% of the catalyst mass, nitrogen-doped mesoporous carbon accounting for 2% of the catalyst mass and SiC accounting for 3%.

[0076] Catalyst performance test: The above catalyst was reduced at 500°C for 10 hours and then the carbon dioxide methanation reaction performance was evaluated. The reaction evaluation set the reaction temperature to 250°C, the reaction pressure to 2.5MPa, the raw gas composition to 20%-CO, 80%-H2, and the H2S content to 20ppm.

[0077] The reactor filling structure is: 2 layers of inert filler layers (M layer and N layer) and 3 layers of catalyst active layers (A layer, B layer, C layer from top to bottom). The first layer A is filled with WH-HS catalyst, which is in the shape of a four-hole wheel and has an outer diameter of 6mm; the second layer B is filled with WH-LS, which is in the shape of a cylinder and has an outer diameter of 3mm; the third layer C is filled with WH-HM and WH-LS catalysts in a 3:1 ratio, and both catalysts are spherical in shape and have an outer diameter of 4mm.

[0078] Catalyst loading performance test:

[0079] The reaction pressure is 2.5MPa, the raw gas composition is 15% -CO2, the hydrogen-carbon ratio is 4:1, the rest are N2 / CH4 and other components, the H2S content is 5ppm, and it is preheated to 250℃ before entering the catalyst active layer. The hot spot temperature appears in the second layer (B layer) at 410℃, and the gas temperature after passing through the C layer is 300℃. The CO2 conversion rate is ≥99.5%, and the CH4 selectivity is ≥99.5%. After continuous operation for 1000h, the hot spot position has not moved significantly and the catalyst activity remains unchanged.

[0080] Example 5

[0081] WH-HS catalyst: 25 g nitrogen-doped mesoporous carbon (size > 500 mesh, 1100 m 2 / g, average pore size 5.5nm, nitrogen content 5%, of which pyridinic nitrogen 44.51%, pyrrolic nitrogen 26.59%, graphite nitrogen 20.52%, oxidized nitrogen 8.38%) and 25g SiC (size> 500 mesh) were dispersed at high speed in a sodium nitrate salt solution (the mass concentration of the sodium nitrate salt solution was 5%, the ultrasonic frequency was controlled to be 40kHz, and the power was 800kW) to form a suspension (the solid-liquid mass ratio of the suspension was 1:20); then the suspension was heated to 50°C, 58.2g nickel nitrate, 95.6g aluminum nitrate, 6.9g zirconium nitrate, 4.1g manganese nitrate, 7.6g cerium nitrate, and 12.3g ammonium molybdate were configured into a precursor salt solution, and sodium carbonate was configured as a precipitant solution (take The molar ratio of the precursor salt to sodium carbonate is 0.1:1), which is preheated to 80°C by electric heating, and then dripped into the suspension in parallel (the dripping speed is completed within 50 minutes, and the stirring speed is 600rpm), the precipitation reaction is started, the pH of the solution is maintained at 7-8 and stirring is continued for 1 hour; cobalt and zinc salt solution, containing 5.8g of cobalt nitrate and 16.7g of zinc nitrate, is added to the above solution, and an alkaline precipitant is added to maintain the pH of the solution at 7-8, and stirring is continued for 1-2 hours; the precipitate is filtered, pulped, and washed for multiple cycles until the conductivity of the filtrate is 50μS / cm, and then dried, and then calcined to obtain a catalyst powder; the calcination temperature is 600°C, the calcination time is 6h, and the calcination atmosphere is nitrogen.

[0082] Calculated by the mass of oxides, nickel oxide, molybdenum oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide, cobalt oxide and zinc oxide account for 15%, 10%, 13%, 2%, 1%, 3%, 1.5% and 4.5% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 25% of the catalyst mass, respectively.

[0083] WH-LS catalyst: The preparation method is the same as that of WH-HS catalyst, except that the added amounts of Mo, Co and Zn are different.

[0084] The catalyst powder, calculated by the mass of oxides, nickel oxide, molybdenum oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide, cobalt oxide and zinc oxide account for 25%, 5%, 40%, 4%, 1%, 3%, 0.5% and 1.5% of the catalyst mass respectively, and nitrogen-doped mesoporous carbon and SiC account for 10% of the catalyst mass each.

[0085] WH-HM catalyst: The preparation method is the same as that of WH-HS catalyst, but it does not contain Mo, Co, or Zn.

[0086] The catalyst powder, calculated by the mass of oxides, comprises nickel oxide, aluminum oxide, zirconium oxide, manganese oxide and cerium oxide respectively accounting for 35%, 50%, 5%, 1% and 4% of the catalyst mass, nitrogen-doped mesoporous carbon accounting for 2% of the catalyst mass and SiC accounting for 3%.

[0087] Catalyst performance test: The above catalyst was reduced at 500°C for 10 hours and then the carbon dioxide methanation reaction performance was evaluated. The reaction evaluation set the reaction temperature to 250°C, the reaction pressure to 2.5MPa, the raw gas composition to 20%-CO, 80%-H2, and the H2S content to 20ppm. The reaction results are shown in Table 1.

[0088] The reactor filling structure is: 2 layers of inert filler layers (M layer and N layer) and 6 layers of catalyst active layers (from top to bottom, A layer, B layer, C layer, D layer, E layer, and F layer). The first layer A is filled with WH-HS catalyst, which is in the shape of a four-hole wheel and has an outer diameter of 6mm; the second layer B is filled with WH-LS, which is cylindrical and has an outer diameter of 3mm; the third layer C is filled with WH-HM and WH-LS catalysts at a ratio of 3:1, both catalysts are spherical, and the outer diameter of the catalyst is 4mm; the fourth layer D is filled with WH-HM and WH-LS catalysts at a ratio of 6:1; the fifth layer E is filled with WH-HM and WH-LS catalysts at a ratio of 8:1, both catalysts are cylindrical, and the outer diameter of the catalyst is 3mm; the sixth layer F is filled with WH-HM and WH-LS catalysts at a ratio of 15:1, both catalysts are spherical, and the outer diameter of the catalyst is 3mm. Catalyst loading performance test:

[0089] The reaction pressure is 2.5MPa, the raw gas composition is 15% -CO2, the hydrogen-carbon ratio is 4:1, the rest are N2 / CH4 and other components, the H2S content is 5ppm, and it is preheated to 250℃ before entering the catalyst active layer. The hot spot temperature appears in the third layer (C layer) at 395℃, and the gas temperature after passing through the F layer is 285℃. The CO2 conversion rate is ≥99.5%, and the CH4 selectivity is ≥99.5%. After continuous operation for 1000h, the hot spot position has not moved significantly and the catalyst activity remains unchanged.

[0090] Example 6

[0091] WH-HS catalyst: 30 g nitrogen-doped mesoporous carbon (size > 500 mesh, 1100 m 2 / g, average pore size 5.5nm, nitrogen content 5%, of which pyridinic nitrogen 44.51%, pyrrolic nitrogen 26.59%, graphite nitrogen 20.52%, oxidized nitrogen 8.38%) and 20g SiC (size> 500 mesh) were dispersed at high speed in a sodium nitrate salt solution (the mass concentration of the sodium nitrate salt solution was 5%, the ultrasonic frequency was controlled to be 40kHz, and the power was 800kW) to form a suspension (the solid-liquid mass ratio of the suspension was 1:20); then the suspension was heated to 50°C, 58.2g nickel nitrate, 95.6g aluminum nitrate, 6.9g zirconium nitrate, 4.1g manganese nitrate, 7.6g cerium nitrate, and 12.3g ammonium molybdate were configured into a precursor salt solution, and sodium carbonate was configured as a precipitant solution (take The molar ratio of the precursor salt to sodium carbonate is 0.1:1), which is preheated to 80°C by electric heating, and then dripped into the suspension in parallel (the dripping speed is completed within 50 minutes, and the stirring speed is 600rpm), the precipitation reaction is started, the pH of the solution is maintained at 7-8 and stirring is continued for 1 hour; cobalt and zinc salt solution, containing 5.8g of cobalt nitrate and 16.7g of zinc nitrate, is added to the above solution, and an alkaline precipitant is added to maintain the pH of the solution at 7-8, and stirring is continued for 1-2 hours; the precipitate is filtered, pulped, and washed for multiple cycles until the conductivity of the filtrate is 50μS / cm, and then dried, and then calcined to obtain a catalyst powder; the calcination temperature is 600°C, the calcination time is 6h, and the calcination atmosphere is nitrogen.

[0092] Calculated by the mass of oxides, nickel oxide, molybdenum oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide, cobalt oxide and zinc oxide account for 15%, 10%, 13%, 2%, 1%, 3%, 1.5% and 4.5% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 30% and 20% of the catalyst mass, respectively.

[0093] WH-LS catalyst: The preparation method is the same as that of WH-HS catalyst, except that the added amounts of Mo, Co and Zn are different.

[0094] The catalyst powder, calculated by the mass of oxides, nickel oxide, molybdenum oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide, cobalt oxide and zinc oxide account for 25%, 5%, 40%, 4%, 1%, 3%, 0.5% and 1.5% of the catalyst mass respectively, and nitrogen-doped mesoporous carbon and SiC account for 12% and 8% of the catalyst mass respectively.

[0095] WH-HM catalyst: The preparation method is the same as that of WH-HS catalyst, but it does not contain Mo, Co, or Zn.

[0096] The catalyst powder, calculated by the mass of oxides, comprises nickel oxide, aluminum oxide, zirconium oxide, manganese oxide and cerium oxide, respectively, 35%, 50%, 5%, 1% and 4% of the catalyst mass, nitrogen-doped mesoporous carbon accounts for 1.5% of the catalyst mass, and SiC accounts for 3.5%.

[0097] Catalyst performance test: The above catalyst was reduced at 500°C for 10 hours and then the carbon dioxide methanation reaction performance was evaluated. The reaction evaluation set the reaction temperature to 250°C, the reaction pressure to 2.5MPa, the raw gas composition to 20%-CO, 80%-H2, and the H2S content to 20ppm. The reaction results are shown in Table 1.

[0098] The reactor filling structure is: 2 layers of inert filler layers (M layer and N layer) and 6 layers of catalyst active layers (from top to bottom, A layer, B layer, C layer, D layer, E layer, and F layer). The first layer A is filled with WH-HS catalyst, which is in the shape of a four-hole wheel and has an outer diameter of 6mm; the second layer B is filled with WH-LS, which is cylindrical and has an outer diameter of 3mm; the third layer C is filled with WH-HM and WH-LS catalysts at a ratio of 3:1, both catalysts are spherical, and the outer diameter of the catalyst is 4mm; the fourth layer D is filled with WH-HM and WH-LS catalysts at a ratio of 6:1; the fifth layer E is filled with WH-HM and WH-LS catalysts at a ratio of 8:1, both catalysts are cylindrical, and the outer diameter of the catalyst is 3mm; the sixth layer F is filled with WH-HM and WH-LS catalysts at a ratio of 15:1, both catalysts are spherical, and the outer diameter of the catalyst is 3mm. Catalyst loading performance test:

[0099] The reaction pressure is 2.5MPa, the raw gas composition is 15% -CO2, the hydrogen-carbon ratio is 4:1, the rest are N2 / CH4 and other components, the H2S content is 5ppm, and it is preheated to 250℃ before entering the catalyst active layer. The hot spot temperature appears in the third layer (C layer) with a temperature of 385℃. After passing through the F layer, the gas temperature is 280℃, the CO2 conversion rate is ≥99.5%, the CH4 selectivity is ≥99.5%, and it runs continuously for 1000h. The hot spot position has not moved significantly and the catalyst activity remains unchanged.

[0100] Example 7

[0101] WH-HS catalyst: 15 g nitrogen-doped mesoporous carbon (size > 500 mesh, 1100 m 2 / g, average pore size 5.5nm, nitrogen content 5%, of which pyridinic nitrogen 44.51%, pyrrolic nitrogen 26.59%, graphite nitrogen 20.52%, oxidized nitrogen 8.38%) and 25g SiC (size> 500 mesh) were dispersed at high speed in a sodium nitrate salt solution (the mass concentration of the sodium nitrate salt solution was 5%, the ultrasonic frequency was controlled to be 40kHz, and the power was 800kW) to form a suspension (the solid-liquid mass ratio of the suspension was 1:20); then the suspension was heated to 50°C, 58.2g nickel nitrate, 132.4g aluminum nitrate, 6.9g zirconium nitrate, 4.1g manganese nitrate, 7.6g cerium nitrate, and 15.9g ammonium molybdate were configured into a precursor salt solution, and sodium carbonate was configured as a precipitant solution (take The molar ratio of the precursor salt to sodium carbonate is 0.1:1), which is preheated to 80°C by electric heating, and then dripped into the suspension in parallel (the dripping speed is completed within 50 minutes, and the stirring speed is 600rpm), and the precipitation reaction is started, and the pH of the solution is maintained at 7-8 and stirred for 1 hour; a salt solution of cobalt and zinc, containing 11.6g of cobalt nitrate and 18.5g of zinc nitrate, is added to the above solution, and an alkaline precipitant is added to maintain the pH of the solution at 7-8, and stirring is continued for 1-2 hours; the precipitate is filtered, pulped, and washed for multiple cycles until the conductivity of the filtrate is 50μS / cm, and then dried, and then calcined to obtain a catalyst powder; the calcination temperature is 600°C, the calcination time is 6h, and the calcination atmosphere is nitrogen.

[0102] Calculated by the mass of oxides, nickel oxide, molybdenum oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide, cobalt oxide and zinc oxide account for 15%, 13%, 18%, 2%, 1%, 3%, 3% and 5% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 15% and 25% of the catalyst mass, respectively.

[0103] WH-LS catalyst: The preparation method is the same as that of WH-HS catalyst, the difference is that the amount of Mo, Co and Zn added is different.

[0104] The catalyst powder, calculated by the mass of oxides, nickel oxide, molybdenum oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide, cobalt oxide and zinc oxide account for 27%, 5%, 36%, 4%, 1%, 3%, 0.5% and 1.5% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 12% and 10% of the catalyst mass, respectively.

[0105] WH-HM catalyst: The preparation method is the same as that of WH-HS catalyst, but it does not contain Mo, Co, or Zn.

[0106] The catalyst powder, calculated by the mass of oxides, comprises nickel oxide, aluminum oxide, zirconium oxide, manganese oxide and cerium oxide, respectively, 35%, 50%, 5%, 2% and 3% of the catalyst mass, nitrogen-doped mesoporous carbon 2.5% and SiC 2.5%.

[0107] Catalyst performance test: The above catalyst was reduced at 500°C for 10 hours and then the carbon dioxide methanation reaction performance was evaluated. The reaction evaluation set the reaction temperature to 250°C, the reaction pressure to 2.5MPa, the raw gas composition to 20%-CO, 80%-H2, and the H2S content to 20ppm. The reaction results are shown in Table 1.

[0108] The reactor filling structure is: 2 layers of inert filler layers (M layer and N layer) and 6 layers of catalyst active layers (from top to bottom, A layer, B layer, C layer, D layer, E layer, and F layer). The first layer A is filled with WH-HS catalyst, which is in the shape of a four-hole wheel and has an outer diameter of 6mm; the second layer B is filled with WH-LS, which is cylindrical and has an outer diameter of 3mm; the third layer C is filled with WH-HM and WH-LS catalysts at a ratio of 3:1, both catalysts are spherical, and the outer diameter of the catalyst is 4mm; the fourth layer D is filled with WH-HM and WH-LS catalysts at a ratio of 5:1, and the fifth layer E is filled with WH-HM and WH-LS catalysts at a ratio of 6:1, both catalysts are cylindrical, and the outer diameter of the catalyst is 3mm; the sixth layer F is filled with WH-HM and WH-LS catalysts at a ratio of 12:1, both catalysts are spherical, and the outer diameter of the catalyst is 3mm. Catalyst loading performance test:

[0109] The reaction pressure is 2.5MPa, the raw gas composition is 15% -CO2, the hydrogen-carbon ratio is 4:1, the rest are N2 / CH4 and other components, the H2S content is 5ppm, and it is preheated to 250℃ before entering the catalyst active layer. The hot spot temperature appears in the third layer (C layer) at 390℃, and the gas temperature after passing through the F layer is 282℃. The CO2 conversion rate is ≥99.5%, and the CH4 selectivity is ≥99.5%. After continuous operation for 1000h, the hot spot position has not moved significantly and the catalyst activity remains unchanged.

[0110] Example 8

[0111] WH-HS catalyst: 14 g nitrogen-doped mesoporous carbon (size > 500 mesh, 1100 m 2 / g, average pore size 5.5nm, nitrogen content 5%, of which pyridinic nitrogen 44.51%, pyrrolic nitrogen 26.59%, graphite nitrogen 20.52%, oxidized nitrogen 8.38%) and 26g SiC (size> 500 mesh) were dispersed at high speed in a sodium nitrate salt solution (the mass concentration of the sodium nitrate salt solution was 5%, the ultrasonic frequency was controlled to be 40kHz, and the power was 800kW) to form a suspension (the solid-liquid mass ratio of the suspension was 1:20); then the suspension was heated to 50°C, 54.3g nickel nitrate, 132.4g aluminum nitrate, 6.9g zirconium nitrate, 4.1g manganese nitrate, 7.6g cerium nitrate, and 17.2g ammonium molybdate were configured into a precursor salt solution, and sodium carbonate was configured as a precipitant solution (take The molar ratio of the precursor salt to sodium carbonate is 0.1:1), which is preheated to 80°C by electric heating, and then dripped into the suspension in parallel (the dripping speed is completed within 50 minutes, and the stirring speed is 600rpm), and the precipitation reaction is started, and the pH of the solution is maintained at 7-8 and stirred for 1 hour; a salt solution of cobalt and zinc, containing 11.6g of cobalt nitrate and 18.5g of zinc nitrate, is added to the above solution, and an alkaline precipitant is added to maintain the pH of the solution at 7-8, and stirring is continued for 1-2 hours; the precipitate is filtered, pulped, and washed for multiple cycles until the conductivity of the filtrate is 50μS / cm, and then dried, and then calcined to obtain a catalyst powder; the calcination temperature is 600°C, the calcination time is 6h, and the calcination atmosphere is nitrogen.

[0112] Calculated by the mass of oxides, nickel oxide, molybdenum oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide, cobalt oxide and zinc oxide account for 14%, 14%, 18%, 2%, 1%, 3%, 3% and 5% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 14% and 26% of the catalyst mass, respectively.

[0113] WH-LS catalyst: The preparation method is the same as that of WH-HS catalyst, except that the added amounts of Mo, Co and Zn are different.

[0114] The catalyst powder, calculated by the mass of oxides, nickel oxide, molybdenum oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide, cobalt oxide and zinc oxide account for 25%, 5%, 38%, 4%, 1%, 3%, 0.5% and 1.5% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 11% and 11% of the catalyst mass, respectively.

[0115] WH-HM catalyst: The preparation method is the same as that of WH-HS catalyst, but it does not contain Mo, Co, or Zn.

[0116] The catalyst powder, calculated by the mass of oxides, comprises nickel oxide, aluminum oxide, zirconium oxide, manganese oxide and cerium oxide, respectively, 38%, 47%, 5%, 2% and 3% of the catalyst mass, nitrogen-doped mesoporous carbon 2% and SiC 3%.

[0117] Catalyst performance test: The above catalyst was reduced at 500°C for 10 hours and then the carbon dioxide methanation reaction performance was evaluated. The reaction evaluation set the reaction temperature to 250°C, the reaction pressure to 2.5MPa, the raw gas composition to 20%-CO, 80%-H2, and the H2S content to 20ppm. The reaction results are shown in Table 1.

[0118] The reactor filling structure is: 2 layers of inert filler layers (M layer and N layer) and 6 layers of catalyst active layers (from top to bottom, A layer, B layer, C layer, D layer, E layer, and F layer). The first layer A is filled with WH-HS catalyst, which is in the shape of a four-hole wheel and has an outer diameter of 6mm; the second layer B is filled with WH-LS, which is in the shape of a cylinder and has an outer diameter of 3mm; the third layer C is filled with WH-HM and WH-LS catalysts at a ratio of 3:1, both catalysts are spherical, and the outer diameter of the catalyst is 4mm; the fourth layer D is filled with WH-HM and WH-LS catalysts at a ratio of 5:1; the fifth layer E is filled with WH-HM and WH-LS catalysts at a ratio of 6:1, both catalysts are cylindrical, and the outer diameter of the catalyst is 3mm; the sixth layer F is filled with WH-HM and WH-LS catalysts at a ratio of 12:1, both catalysts are spherical, and the outer diameter of the catalyst is 3mm.

[0119] Catalyst loading performance test:

[0120] The reaction pressure is 2.5MPa, the raw gas composition is 15% -CO2, the hydrogen-carbon ratio is 4:1, the rest are N2 / CH4 and other components, the H2S content is 5ppm, and it is preheated to 250℃ before entering the catalyst active layer. The hot spot temperature appears in the third layer (C layer) with a temperature of 388℃. After passing through the F layer, the gas temperature is 283℃, the CO2 conversion rate is ≥99.5%, the CH4 selectivity is ≥99.5%, and it runs continuously for 1000h. The hot spot position does not move significantly and the catalyst activity remains unchanged.

[0121] Comparative Example 1

[0122] Catalyst is the same as in Example 1

[0123] The filling structure of the reactor is: two layers of inert filler (M layer and N layer) and one layer of catalyst active layer are used, all of which are filled with WH-HS catalyst, and the catalysts used are all spherical in shape.

[0124] The reaction pressure is 2.5MPa, the raw gas composition is 15%-CO2, the hydrogen-carbon ratio is 4:1, the rest is N2 / CH4 and other components, the H2S content is 5ppm, and it is preheated to 250℃ before entering the catalyst active layer. The hot spot temperature appears at 3 / 5 of the catalyst bed height, and the temperature is 305℃. After passing through bed F, the gas temperature is 220℃, the CO2 conversion rate is ≥42.5%, and the CH4 selectivity is ≥95.5%. After continuous operation for 1000h, the hot spot position remains unchanged, and the catalyst activity remains unchanged

[0125] Comparative Example 2

[0126] Catalyst is the same as in Example 1

[0127] The filling structure of the reactor is: two layers of inert filler (M layer and N layer) and one layer of catalyst active layer are used, all of which are filled with WH-LS catalyst, and the catalysts used are all cylindrical in shape.

[0128] The reaction pressure is 2.5MPa, the raw gas composition is 15%-CO2, the hydrogen-carbon ratio is 4:1, the rest is N2 / CH4 and other components, the H2S content is 5ppm, and it is preheated to 250℃ before entering the catalyst active layer. The hot spot temperature appears at the first 1 / 6 of the catalyst bed height, the temperature is 365℃, and the gas temperature after passing through the bed is 270℃, the CO2 conversion rate is ≥80.5%, and the CH4 selectivity is ≥98.5%. After continuous operation for 1000h, the hot spot position moves slightly downward, the hot spot temperature is 360℃, the CO2 conversion rate is ≥75.5%, and the CH4 selectivity is ≥98.5%.

[0129] Comparative Example 3

[0130] The filling structure of the reactor is: two layers of inert filler (M layer and N layer) and one layer of catalyst active layer are used, all of which are filled with WH-HM catalyst, and the catalysts used are all cylindrical in shape.

[0131] The reaction pressure is 2.5MPa, the raw gas composition is 15%-CO2, the hydrogen-carbon ratio is 4:1, the rest is N2 / CH4 and other components, the H2S content is 5ppm, and it is preheated to 250℃ and enters the catalyst active layer. The hot spot temperature appears at 1 / 8 of the catalyst bed, the temperature is 350℃, and the gas temperature after passing through the bed is 280℃, CO2 conversion rate ≥98.5%, CH4 selectivity ≥99.5%. After 200h, the hot spot position moves down to about 1 / 2 of the bed, the temperature is 310℃, and the gas temperature after passing through bed F is 220℃, CO2 conversion rate ≥50.5%, CH4 selectivity ≥99.5%, which shows that the high-activity catalyst that is not resistant to sulfur has poor catalyst stability in an atmosphere containing hydrogen sulfide.

[0132] Comparative Example 4

[0133] The filling structure of the reactor is: 2 layers of inert filler layers (M layer and N layer) and 1 layer of catalyst active layer. The ratio of WH-HS catalyst to WH-LS catalyst in the active layer is 1:1. The shape of WH-HS catalyst is a four-hole wheel shape with an outer diameter of 6mm, and the shape of WH-LS catalyst is a four-hole wheel shape with an outer diameter of 6mm.

[0134] The reaction pressure is 2.5MPa, the raw gas composition is 15%-CO2, the hydrogen-carbon ratio is 4:1, the rest is N2 / CH4 and other components, the H2S content is 5ppm, and it is preheated to 250℃ before entering the catalyst active layer. The hot spot temperature appears in the front 1 / 3 of the catalyst bed, and the temperature is 355℃. The gas temperature after passing through the bed is 275℃, the CO2 conversion rate is ≥96.5%, and the CH4 selectivity is ≥93.5%. After continuous operation for 1000h, the hot spot temperature, position and catalyst activity remain basically unchanged. Comparative Example 5

[0135] The WH-HS catalyst is the same as in Example 1, except that it does not contain the Co-Zn coating.

[0136] The catalyst loading ratio is the same as that in Example 1.

[0137] The reaction pressure is 2.5MPa, the raw gas composition is 15%-CO2, the hydrogen-carbon ratio is 4:1, the rest are N2 / CH4 and other components, the H2S content is 5ppm, and it is preheated to 250℃ before entering the catalyst active layer. The hot spot temperature appears in the third layer (C layer) with a temperature of 385℃. After passing through bed F, the gas temperature is 280℃, the CO2 conversion rate is ≥99.5%, and the CH4 selectivity is ≥99.5%. After continuous operation for 1000h, the hot spot position shifts slightly downward, and the hot spot temperature drops to 375℃. The catalyst activity decreases, the CO2 conversion rate is ≥93.5%, and the CH4 selectivity is ≥99.5%.

[0138] Comparative Example 6

[0139] The WH-HS catalyst is the same as in Example 1, except that it does not contain Mo.

[0140] The catalyst loading ratio is the same as in Example 1

[0141] The reaction pressure is 2.5MPa, the raw gas composition is 15%-CO2, the hydrogen-carbon ratio is 4:1, the rest are N2 / CH4 and other components, the H2S content is 5ppm, and it is preheated to 250℃ before entering the catalyst active layer. The hot spot temperature appears in the third layer (C layer) with a temperature of 385℃. After passing through bed F, the gas temperature is 280℃, the CO2 conversion rate is ≥99.5%, and the CH4 selectivity is ≥99.5%. After continuous operation for 1000h, the hot spot position shifts slightly downward, the hot spot temperature drops to 370℃, and the catalyst activity decreases significantly, the CO2 conversion rate is ≥82.5%, and the CH4 selectivity is ≥99.5%.

[0142] From the evaluation of sulfur resistance activity of the catalysts in Examples 1 to 8 and Comparative Examples 1 to 6 and the actual loading application, the active component Mo and Co-Zn coating are both beneficial to enhancing the sulfur resistance of the catalyst. Long-term use of a single catalyst will result in poor sulfur resistance stability of the high-activity catalyst, while the activity and selectivity of the sulfur-resistant catalyst are relatively low. By mixing the three catalysts in different proportions and in different orders, the bed heats up slowly, the hot spot temperature is controllable, the reaction activity is high, the methane selectivity is high, and the overall catalyst bed has high sulfur resistance stability.

[0143] Table 1 Catalyst evaluation results

[0144]

Claims

1. A sulfur-tolerant carbon dioxide methanation catalyst, characterized in that: The catalyst comprises a carrier, a carrier modifier, an active component, an auxiliary agent and a coating; the carrier comprises Al2O3 and ZrO2, the carrier modifier is nitrogen-doped mesoporous carbon and / or silicon carbide, the active component comprises NiO and MoO3, the auxiliary agent comprises CeO2 and MnO2, and the coating is a Co-Zn coating; in terms of the total weight percentage of the catalyst: the content of Al2O3 is 10-70wt%, the content of ZrO2 is 2-15wt%, the content of the carrier modifier is 1-75wt%, the content of the active component is 10-50wt%, the mass ratio of NiO:MoO3 is 1-5:0-1, the content of the auxiliary agent is 1-5wt%, the mass ratio of CeO2:MnO2 is 1-5:1, the content of the Co-Zn coating is 0-10wt%, and the mass ratio of CoO:ZnO is 1:1-3.

2. The sulfur-resistant carbon dioxide methanation catalyst according to claim 1, characterized in that: When the carrier modifier is a mixture of nitrogen-doped mesoporous carbon and silicon carbide, the mass fraction ratio of nitrogen-doped mesoporous carbon to silicon carbide is 1-3:1-3.

3. The sulfur-resistant carbon dioxide methanation catalyst according to claim 1, characterized in that: The nitrogen-doped mesoporous carbon has a nitrogen content of 1.5-12% and a specific surface area of ​​800-1200 m 2 / g, and the average pore size is 4 to 8.1 nm.

4. A method for preparing the catalyst as claimed in claim 1, characterized in that: The preparation method is as follows: 1) stirring and ultrasonically dispersing the support modifier in the salt solution to form a suspension, and heating the suspension to 50-80° C. for standby use; dissolving the precursor salt in deionized water to form a precursor salt solution, heating the precursor salt solution and the precipitant solution to 50-80° C. respectively, and dripping the precursor salt solution and the precipitant solution into the suspension in parallel for precipitation reaction, maintaining the pH of the solution at 7-8 and continuously stirring; 2) Add cobalt and zinc salt solutions to the solution, add alkaline precipitant, maintain the pH of the solution at 7-8, and continue stirring; 3) After precipitation, the catalyst is aged, washed, filtered, dried, calcined and then formed into tablets to obtain the desired catalyst.

5. The method for preparing the catalyst according to claim 4, characterized in that: In the step 1), the molar ratio of the precursor salt to the precipitant is 0.1 to 10:1, the mass concentration of the precursor salt solution is 0.5 to 5%; and the solid-liquid mass ratio of the suspension is 1:20 to 1:

50.

6. The method for preparing the catalyst according to claim 4, characterized in that: The precursor salt is composed of nickel nitrate, manganese nitrate, cerium nitrate, aluminum nitrate, zirconium nitrate and ammonium molybdate; the Co salt is cobalt nitrate, the Zn salt is zinc nitrate; and the precipitant is at least one of sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate.

7. The method for preparing the catalyst according to claim 4, characterized in that: In the step 3), the calcination temperature is 300-600° C., the calcination time is 4-12 hours, and the calcination atmosphere is nitrogen.

8. Use of the catalyst as claimed in claim 1, characterized in that: A catalyst active layer is loaded in the reactor, and an inert filler layer is arranged at both ends of the catalyst active layer, wherein the catalyst active layer is composed of a WH-HS catalyst and / or a WH-LS catalyst and / or a WH-HM catalyst; The WH-HS catalyst is a highly sulfur-resistant methanation catalyst: the content of Al2O3 is 10-30wt%, the content of ZrO2 is 2-5wt%; the content of the carrier modifier is 40-70wt%, the mass ratio of nitrogen-doped mesoporous carbon: silicon carbide is 1-3:1-3; the content of the active component is 10-30wt%, the mass ratio of NiO:MoO3 is 1-3:1; the content of the auxiliary agent is 1-5wt%, the mass ratio of CeO2:MnO2 is 1-5:1; the content of the Co-Zn coating is 5-10wt%, and the mass ratio of CoO:ZnO is 1:1-3; WH-LS catalyst is a low sulfur-resistant methanation catalyst: the content of Al2O3 is 20-50wt%, the content of ZrO2 is 2-10wt%, the content of carrier modifier is 15-30wt%, the mass ratio of nitrogen-doped mesoporous carbon: silicon carbide is 1-3:1-3; the content of active component is 20-40wt%, the mass ratio of NiO:MoO3 is 5-10:1; the content of auxiliary agent is 1-5wt%, the mass ratio of CeO2:MnO2 is 1-5:1; the content of Co-Zn coating is 1-5wt%, and the mass ratio of CoO:ZnO is 1:1-3; WH-HM catalyst is a highly active methanation catalyst: the content of Al2O3 is 40-60wt%, the content of ZrO2 is 2-10wt%, the content of carrier modifier is 1-10wt%, the mass ratio of nitrogen-doped mesoporous carbon: silicon carbide is 1-3:1-3, the content of active component NiO is 25-50wt%, the content of auxiliary agent is 1-5wt%, and the mass ratio of CeO2:MnO2 is 1-5:

1.

9. The use of the catalyst according to claim 8, characterized in that: The catalyst active layers are 3 to 6 layers, all arranged along the flow direction of the airflow; the catalyst active layer of the first layer is a WH-HS catalyst, the catalyst active layer of the second layer is a WH-LS catalyst, and the catalyst active layers of the remaining layers are mixed catalysts of WH-HM catalysts and WH-LS catalysts, the mass ratio of the WH-HM catalyst to the WH-LS catalyst is 3:0.1-1, and the mass ratio of the WH-HM catalyst increases layer by layer along the flow direction of the airflow; the catalysts in the catalyst active layers of the same layer have the same shape; the reactor is a shell-and-tube temperature-controlled reactor, the catalyst is loaded in the shell layer, and the water channel supplies and transfers heat through the tube layer.

10. The use of the catalyst according to claim 8, characterized in that: In the reactor, the bed temperature is 240-290°C, the hot spot temperature is 380-500°C, and the outflow temperature of the reactor gas outlet is 250-300°C.

Citation Information

Patent Citations

  • Method for preparing hydrophobic composite membrane

    CN103551053A

  • Isothermal reactor with function of conveniently and quickly replacing catalyst, and technological method of isothermal reactor

    CN110237778A

  • Sulfur-resistant carbon dioxide methanation catalyst and its preparation method

    CN112642440B

  • Preparation method of isothermal fixed bed methanation catalyst

    CN113289663A

  • Adiabatic-isothermal methanation reactor

    CN204247177U

Cited By

  • Coated platinum-carbon catalyst, preparation method thereof and hydrogen fuel cell

    CN122417929A